Hubungan Self Monitoring Dengan Impulsive Buying Terhadap Produk Fashion Pada Remaja - Anin F, Anastasia; BS, Rasimin; Atamimi, Nuryati (Faculty of Psychology, Universitas Gadjah Mada, 2008)
The aim of this study is to investigate the relationship between self monitoring and impulsive buying towards fashion product on adolescent. It was hypothesized that there is a positive relationship between self monitoring and impulsive buying towards fashion product on adolescent. The subjects of this study (N = 92) were the students of Faculty of Economy Gadjah Mada University, Yogyakarta. Two questionnaires were applied to measure self monitoring and impulsive buying towards fashion product on adolescent. The result indicated a positive and significant relationship between attitude towards modernization and entrepreneurship on adolescent (r = 0,402; p = 0,000), meaning that the research hypothesis was accepted. The determination coefficient was 0,162 indicating that the self monitoring contributes 16,2% to the impulsibbuying toward fashion product on adolescent.